The Application of Artificial Bee Colony and Gravitational Search Algorithm in Reservoir Optimization - Ahmad, A.; Razali, S.F.M.; Mohamed, Z.S.; El-Shafie, Ahmed (Springer Verlag, 2016)
This paper presented the application of Artificial Bee Colony (ABC) and Gravitational Search Algorithm (GSA) in reservoir optimization. ABC is an algorithm based on the foraging behaviour of bee while GSA imitates the gravitational processes. These algorithms were used to minimize the irrigation release deficit for Timah Tasoh Dam located at the Northern part of Peninsular Malaysia. Results proved the superiority of the ABC compared to GSA with regards to faster convergence rate, stability, higher reliability and lower vulnerability indexes, while GSA is better in the resiliency indicator measure. Finally, both algorithms can be used to solve reservoir optimization problem with their own unique capability and to improve the performance of the reservoir compared to the existing reservoir standard operation procedure.